(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Vinpocetine has been shown to protect against degenerative senile cerebral dysfunction via enhancement of cerebral blood flow, cognition and neuroprotective action. This study sought to investigate the protective effect of vinpocetine against haloperidol-induced catalepsy in mice. Vinpocetine (5, 10 or 20 mg/kg, p.o.) was administered 1 h after haloperidol injection for 21 consecutive days. Effect on motor coordination, depressive-like behaviour and working memory were assessed with rotarod, forced swim (FST) and Y-maze tests, respectively. Brains were collected on day 21 for biochemical estimation of nitrosative and oxidative stress parameters. Vinpocetine (10 or 20 mg/kg, p.o.) significantly reversed haloperidol-induced motor deficit in rotarod test and open field test and reduced the duration of catalepsy during acute and chronic catalepsy tests as compared to trihexylphenidyl but failed to reverse haloperidol-induced memory deficit in the Y-maze test. Haloperidol-induced increase in malondialdehyde and nitrite generation as well as deficits in antioxidant enzymes activities were attenuated by chronic administration of vinpocetine. These findings suggest that vinpocetine protects against haloperidol-induced catalepsy and motor deficits through attenuation of oxidative/nitrosative stress.